The Cyber Solidarity Act: Framework and Perspectives for the New EU-Wide Cybersecurity Solidarity Mechanism Under the EU Legal System - Susanna Villani (European Journal of Risk Regulation)
Cybersecurity is a concern to be tackled not only by individual States but also by the European Union as a whole. Building on the recent adoption of Regulation (EU) 2025/38, the so-called Cyber Solidarity Act, the study intends to analyse the creation of a supranational capacity to prevent and respond to cyber incidents, by answering the following questions: how and to what extent is solidarity concretely declined in the act in question? How do the mechanisms provided for by this act concretely interact with the Member States’ prerogatives in the broader security domain?